Mean Carrying Angle of Elbow in Children Less Than Ten Years of Age - Zulfiqar Ullah, Ahmadzeb, Akhtar Hussain, Farmanullah Khan, Shehriyar Khan, Mohammad Shoaib Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The median axes of the arm and forearm form an angle known as carrying angle when fully supinated and extended. This posture is crucial while carrying objects because it enables the forearms to pass across the hips in swing motions when walking Objective: To find out the mean carrying angle of elbow in children less than ten years of age. Methodology: This study was Cross Sectional Study carried out at the Outpatient Department of Orthopedic Surgery, Khyber Teaching Hospital, Peshawar for duration of six months from 20 Dec, 2021 to 20 Jun, 2022. Goniometer was used for the measurement of the carrying angle. All information such as age, height, weight, length of arm, and carrying angle was documented in a pre-designed Performa. Results: Totally, 250 children were included in this study. On the basis of gender wise distribution, 194 (77.6%) children were recorded as male children and 56 (22.4%) children were recorded as female children. The mean (SD) age, height, length of forearm, weight and carrying angle was 6 (1.05) years, 105.5 (3.75) cm, 18.2 (2.23) cm, 12 (2.84) kg and 8.5 (0.82) degree respectively. Significant association of carrying angle was observed with height, weight, forearm length and limb dominancy (p≤0.05). Conclusion: Our study concluded that age, gender, height, weight and dominant side are important factors that affect the value of the carrying angle. Keywords: Elbow; Carrying Angle; Correlation